2017
DOI: 10.1002/macp.201700303
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Adsorbed Polymer Layers: Preparation, Determination of the Adsorbed Amount and Investigation of the Kinetics of Irreversible Adsorption

Abstract: Irreversibly adsorbed polymer layers represent an intriguing new class of materials with unexpected properties, strongly deviating from what observed in unbounded polymer melts. These extremely thin layers (thickness < few tens of nanometers) are obtained via a short list of successive steps, easily reproducible in a laboratory environment: a polymer melt is placed in contact with an adsorbing substrate and non‐adsorbed chains are washed away by soaking the sample in a good solvent. Importantly, tuning the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…As time progresses within regime I (t 1=2 < 150 s 1=2 ) more polymer chains enter the pores and the dielectric strength increases [Eq. The kinetics of irreversible adsorption were first studied theoretically for functionalized polymers in solution [3] and subsequently generalized for thin polymer films (where confinement is one dimensional) by evaluating the thickness of the adsorbed layer [4][5][6]. It was found that adsorption follows two time regimes; at short annealing times, the thickness (h ads ) increases linearly with time due to the available substrate surface scaling as (h ads ∼ N 1=2 ∼ R g , N is the degree of polymerization).…”
Section: (C) Based On the Lucas-washburn Equation (Lwe)mentioning
confidence: 99%
See 1 more Smart Citation
“…As time progresses within regime I (t 1=2 < 150 s 1=2 ) more polymer chains enter the pores and the dielectric strength increases [Eq. The kinetics of irreversible adsorption were first studied theoretically for functionalized polymers in solution [3] and subsequently generalized for thin polymer films (where confinement is one dimensional) by evaluating the thickness of the adsorbed layer [4][5][6]. It was found that adsorption follows two time regimes; at short annealing times, the thickness (h ads ) increases linearly with time due to the available substrate surface scaling as (h ads ∼ N 1=2 ∼ R g , N is the degree of polymerization).…”
Section: (C) Based On the Lucas-washburn Equation (Lwe)mentioning
confidence: 99%
“…In general, placing macromolecules close to interfaces alter their conformational and dynamic properties [1,2]. Much of this behavior stems from polymer-substrate interactions [3][4][5][6]. Taming the strength of interfacial interactions especially under nonequilibrium conditions (e.g., during flow), will enable the design of polymer interfaces with controlled physical properties (viscosity, glass temperature as well as wettability and adhesion) of importance in applications (organic electronic devices, coatings, membranes).…”
mentioning
confidence: 99%
“…Therefore, continued progress in polymer thin film applications depends upon the ability to determine how processing-induced adsorbed layer growth can impact confined polymer properties. Adsorbed nanolayers of homopolymers, typically isolated via solvent leaching, have been experimentally characterized in terms of thickness, [11,16,[20][21][22] density, [12,13] surface topography, [12,16] and T g . [11,16,23] However, limited consideration has been given to the irreversible adsorption of polymers with heterogeneous compositions.…”
mentioning
confidence: 99%
“…Recently, the peculiar physical properties of polymer chains in close proximity to inorganic solid interfaces have been extensively studied. The thermal mobility of chains at the solid interface has been shown to be extremely depressed, with respect to that in the bulk, because of the confinement effect. Also, chains are irreversibly adsorbed onto the surface of the inorganic solids and thereby cannot be removed, even after washing in a good solvent. This is now recognized as an irreversibly adsorbed insoluble layer. Several groups have hitherto reported that the adsorbed layer grows via thermal annealing at a temperature above the glass-transition temperature ( T g ). , …”
mentioning
confidence: 99%